Motor skills, cognition, and work performance of people with severe mental illness. Issue 12 (5th June 2019) - Lipskaya-Velikovsky, Lena; Elgerisi, Dikla; Easterbrook, Adam; Ratzon, Navah Z.
Abstract: Purpose: Employment offers many benefits to people with mental illness, yet their employment rate is much lower than that of the general population. We investigated the effect of work-related motor skills, neurocognition, and job attitudes on the work performance of people with mental illness, comparing those working in sheltered workshops, with controls working in similar jobs. Methods: Twenty-nine adults with severe mental illness and 27 controls matched by gender and age were enrolled into the study using convenience sampling. They were assessed for gross and fine motor hand functioning, job attitudes, work performance, and cognition. Results: People with mental illness scored lower on work performance, cognitive functioning, and hand dexterity while sitting and working with tools. They were assigned lower job loads than were controls, and perceived the physical environment at work as more constraining than did controls. Assembling motor skills significantly explained the work performance of people with mental illness. Conclusions: The results expand our understanding of the complexities involved in the employment of people with severe mental illness, and point to new paths for improving vocational outcomes of people with severe mental illness, taking into account their motor skills and job attitudes. Implications for rehabilitation: Therapists should be aware that employed people with severe mental illness may have various unmet needs, affecting their work performance and experience of stress. This study results demonstrate importance of motor skills and perception of the work environment for the promotion of vocational outcomes among individuals with severe mental illness. Employment of people with severe mental illness should be viewed from holistic perspective as with general population, rather than focused on traditionally illness-related factors.